Maternal Immunological Adaptation During Normal Pregnancy - Bahaa Abu-Raya; Bahaa Abu-Raya; Bahaa Abu-Raya; Bahaa Abu-Raya; Christina Michalski; Christina Michalski; Christina Michalski; Manish Sadarangani; Manish Sadarangani; Manish Sadarangani; Manish Sadarangani; Pascal M. Lavoie; et al. (Frontiers in Immunology, 2020)
The risk and severity of specific infections are increased during pregnancy due to a combination of physiological and immunological changes. Characterizing the maternal immune system during pregnancy is important to understand how the maternal immune system maintains tolerance towards the allogeneic fetus. This may also inform strategies to prevent maternal fatalities due to infections and optimize maternal vaccination to best protect the mother-fetus dyad and the infant after birth. In this review, we describe what is known about the immunological changes that occur during a normal pregnancy.